Determination of Major and Trace Elements in Lotus Seed by Inductively Coupled Plasma-Mass Spectrometry - Zheng, Chuangmu; Zhang, Yongzhi; Wang, Gangjun; Ye, Xuezhu (Asian Journal of Chemistry, 2012)
The trace elements (V, Cr, Mn, Co, Ni, Zn, Sr, Cd, Pb) and major elements (Na, Mg, Al, K, Ca, Fe) in two lotus seed samples were determined by inductively coupled plasma-mass spectrometry, the contents of major elements in lotus seed are according to order of K > Mg > Ca > Na > Fe > Al and that of trace elements is Mn > Zn > Sr > Ni > Cr > Cd > V > Pb > Co. K is abundance in the lotus seed, the contents of two samples are both over 1000 μg g-1. The contents of Cd, Cr and Pb are lower than 0.06 μg g-1 in the two samples.